Synthesis of silver-doped zinc oxide photocatalyst via solvothermal method for degradation of 4- chlorophenol - Razali, Nur Syafiqa Hazirah (2015)
4-chlorophenol is the one of priority pollutants that must be treated from the environment due to their toxicity and resistant to conventional treatment. Photocatalytic degradation is an advanced oxidation method which has proven to destroy persistent pollutants from water. The photocatalytic activity of ZnO for removal of water pollutant has been well established. In this work, the effect of silver doping on ZnO was studied and its photocatalytic activity on 4-chlorophenol was investigated. Undoped ZnO and silver doped ZnO (Ag-ZnO) photocatalyst were synthesised under mild solvothermal method at 150°C for 3 hours with further calcination at 300°C, with silver concentrations of 0.2, 0.6, 1.0, 1.5 and 2.0 mol%. The synthesised products were characterized by X-ray diffractions (XRD), Field emission- scanning electron microscopy (FESEM), Energy dispersive Xray (EDX) and UV-VIS-NIR spectroscopy. All samples exhibited hexagonal wurtzite ZnO structure with metallic Ag exists interstitially on the ZnO lattice. There was no significant difference in band gap energy of ZnO and Ag-ZnO, which showed that the band gap energy of all samples were 3.15 eV, which is under UV range. The morphologies of the samples were irregular and rodlike shape with crystallite size in range of 70-90 nm. The BET surface area increase in surface area from undoped ZnO (6.54 m2g-1) to 1% Ag-ZnO (9.20 m2g-1) and decrease with higher loading of Ag. Photocatalytic activities of ZnO and Ag-ZnO were investigated by suspension of the photocatalysts in 4-chlorophenol solution under irradiation of UV light and visible light. The result showed that the degradation of 4CP only occurred under UV light irradiation. 0.6% Ag-ZnO photocatalyst showed the highest degradation of 4- chlorophenol than undoped ZnO and Ag-ZnO with other percentage loading. Various basic operational parameters including catalyst amount, initial pH, and initial concentration of 4-Chlorophenol have been investigated. The highest amount of 0.6% Ag-ZnO for the degradation of 4CP is 0.8g. The highest initial concentration of 4CP is 20 ppm, which showed the highest reaction kinetic rate with pseudo-first order reaction. The effect of pH on decomposition of 4CP was found to be influenced by 4CP adsorption and the change of molecular form of 4CP to anionic form. The reusability test of 0.6% Ag-ZnO has been investigated and there is no significant loss of Ag-ZnO and its photocatalytic activity indicates that Ag-ZnO is a stable photocatalysts.